Targeting BRCA1‐BER deficient breast cancer by ATM or DNA‐PKcs blockade either alone or in combination with cisplatin for personalized therapy. Issue 1 (27th August 2014) - Albarakati, Nada; Abdel-Fatah, Tarek M.A.; Doherty, Rachel; Russell, Roslin; Agarwal, Devika; Moseley, Paul; Perry, Christina; Arora, Arvind; Alsubhi, Nouf; Seedhouse, Claire; Rakha, Emad A.; Green, Andrew; et al.
Abstract : BRCA1, a key factor in homologous recombination (HR) repair may also regulate base excision repair (BER). Targeting BRCA1‐BER deficient cells by blockade of ATM and DNA‐PKcs could be a promising strategy in breast cancer. We investigated BRCA1, XRCC1 and pol β protein expression in two cohorts (n = 1602 sporadic and n = 50 germ‐line BRCA1 mutated) and mRNA expression in two cohorts (n = 1952 and n = 249). Artificial neural network analysis for BRCA1‐DNA repair interacting genes was conducted in 249 tumours. Pre‐clinically, BRCA1 proficient and deficient cells were DNA repair expression profiled and evaluated for synthetic lethality using ATM and DNA‐PKcs inhibitors either alone or in combination with cisplatin. In human tumours, BRCA1 negativity was strongly associated with low XRCC1, and low pol β at mRNA and protein levels (p < 0.0001). In patients with BRCA1 negative tumours, low XRCC1 or low pol β expression was significantly associated with poor survival in univariate and multivariate analysis compared to high XRCC1 or high pol β expressing BRCA1 negative tumours (ps < 0.05). Pre‐clinically, BRCA1 negative cancer cells exhibit low mRNA and low protein expression of XRCC1 and pol β. BRCA1‐BER deficient cells were sensitive to ATM and DNA‐PKcs inhibitor treatment either alone or in combination with cisplatin and synthetic lethality was evidenced by DNA double strand breaks accumulation, cell cycle arrest and apoptosis. We conclude that XRCC1 and pol β expression status in BRCA1 negative tumours may have prognostic significance. BRCA1‐BER deficient cells could be targeted by ATM or DNA‐PKcs inhibitors for personalized therapy. Highlights: BRCA1 may regulate base excision repair (BER). BRCA1‐BER deficient cells may be sensitive to blockade of ATM and DNA‐PKcs. We show that low XRCC1/low pol β have prognostic significance in BRCA1−/− tumours. ATM or DNA‐PKcs inhibitors are synthetically lethal in BRCA1‐BER deficient cells. Synthetic lethality is enhanced in combination with cisplatin.